2020
DOI: 10.21608/mjcu.2020.104602
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Monochromatic Infrared Energy Light Versus Laser Therapy in Diabetic Peripheral Neuropathy

Abstract: Diabetic peripheral neuropathy (DPN) is known to be a severe longterm sequelae of diabetes mellitus (DM) and correlated with high morbidity and mortality. There's no widely agreed optimal method for its treatment. Monochromatic Infrared Photo Energy (MIRE) and Low Level Laser Therapy) LLLT) are relatively new modalities of light used to boost the velocity of nerve conduction (NCV), minimize pain and increase peripheral circulation. Purpose: The objective of this study was to compare the effect MIRE versus LLLT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
0
0
Order By: Relevance
“…Chatterjee et al, investigating the effect of 12 sessions of deep tissue laser therapy on painful neuropathy in individuals with type 2 diabetes, reported improvements in function, walking speed, and health-related quality of life (27). Similarly, Sahier et al reported an enhancement in health-related quality of life in individuals with DPN after 12 sessions of LLLT use (36). It's worth noting that neither of these previous studies included a follow-up period after the sessions.…”
Section: Discussionmentioning
confidence: 99%
“…Chatterjee et al, investigating the effect of 12 sessions of deep tissue laser therapy on painful neuropathy in individuals with type 2 diabetes, reported improvements in function, walking speed, and health-related quality of life (27). Similarly, Sahier et al reported an enhancement in health-related quality of life in individuals with DPN after 12 sessions of LLLT use (36). It's worth noting that neither of these previous studies included a follow-up period after the sessions.…”
Section: Discussionmentioning
confidence: 99%